Speech of Army General Raul Castro Ruz - Castro Ruz, Raúl (2017)
First Secretary of the Central Committee of the Communist Party of Cuba and President of the Councils of State and of Ministers, in the VII Summit of the Americas, Panama, April 11, 2015.